NETopathies? Unraveling the Dark Side of Old Diseases through Neutrophils - Mitsios, Alexandros; Arampatzioglou, Athanasios; Arelaki, Stella; Mitroulis, Ioannis; Ritis, Konstantinos (Frontiers in Immunology, 2017)
Neutrophil Extracellular Traps (NETs) were initially described as an antimicrobial mechanism of neutrophils. Over the last decade, several lines of evidence support the involvement of NETs in a plethora of pathological conditions. Clinical and experimental data indicate that NET release constitutes a shared mechanism, which is involved in a different degree in various manifestations of non-infectious diseases. Even though the backbone of NETs is similar, there are differences in their protein load in different diseases, which represents alterations in neutrophil protein expression in distinct disorder-specific microenvironments. The characterization of NET protein load in different NET-driven disorders could be of significant diagnostic and/or therapeutic value. Additionally, it will provide further evidence for the role of NETs in disease pathogenesis and it will enable the characterization of disorders in which neutrophils and NET-dependent inflammation are of critical importance.